Editorial: Gastrointestinal fate and health effects of dietary antioxidants - Abraham, Wall-Medrano (2022)
All mammal cells possess a well-orchestrated redox system tightly connected with other metabolic processes. Many metabolic intermediaries are timely fabricated or destroyed based on their oxidation state and the type and amount of intracellular free radicals regulate the expression of multiple proteins, affecting cell metabolism and survival in a concentration-dependent manner. Also, antioxidant nutrients (e.g., vitamins, minerals, and peptides) and xenobiotics (e.g., phenolic compounds, saponins), play a major role in reducing the odds of cellular oxidative stress, by exerting direct (e.g., radical scavenging), and indirect (e.g., epigenetic action) mechanisms...truncado